The Effect of Active Debate on Oral Communication Skills in Sixth Grade Pancasila Education - Rizky Catur Ananta; Bachtiar Sjaiful Bachri; Fajar Arianto (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The lack of research on the use of active discussion in primary school instruction, despite the fact that it significantly improves students’ oral communication abilities within the framework of Pancasila Education, acted as the catalyst for this investigation. This study aims to investigate the effects of active discussion on the oral communication skills of sixth-grade primary school pupils. This study blended a quantitative design with a quasi-experimental methodology. involving 58 students selected through simple random sampling. Data were collected using oral communication performance tests and observation sheets, then examined using a t-test to ascertain how the outcomes before and after the use of active debate differed. The results demonstrate that students’ oral communication abilities significantly improved following their involvement in the active debate style of instruction. especially in terms of courage to speak, clarity of delivery, and the ability to present arguments logically. These results support the theory of social constructivism, which emphasizes interaction as an important factor in learning. According to the study’s findings, active debate is essential for enhancing primary school pupils’ oral communication abilities. The implications of this research include theoretical contributions to expanding the literature on active learning strategies in elementary schools, as well as practical recommendations for teachers to integrate active debate into Pancasila Education subjects in order to improve students’ 21st-century skills. Furthermore, this study identifies opportunities for future research on the application of active debate in various subjects and different levels of education.